Learning from a successful process evaluation in care homes. (24th June 2021) - Allen, Frances; Darby, Janet; Cook, Marie; Evley, Rachel; Godfrey, Maureen; Horne, Jane; Leighton, Paul; Logan, Pip; Robinson, Katie
Abstract: Introduction: process evaluations (PE) are increasingly used in parallel with randomised controlled trials (RCT) to inform the implementation of complex health interventions. This paper explores the learning accrued from conducting a PE within the Falls in Care Homes Study (FinCH), a large UK RCT. Methods: in the FinCH study, six purposively sampled care homes provided data for the PE, which followed a realist approach. In this study researchers kept written diaries of their experiences in completing the interviews, focus groups and observations. We have reflected on these and present the main themes for discussion. Findings: care home staff were enthusiastic to participate in the PE but researchers found it difficult to collect data due to staff not having time to take part, environmental factors such as no space for focus groups and low levels of research understanding. Researchers found that the expectations of the PE protocol were often unrealistic due to these limitations. Flexible and pragmatic approaches such as interviews in place of focus groups enabled data collection but required a reduced sample size and length of data collection to be accepted by researchers. Conclusion: to enable care home staff to participate in successful PEs, researchers should build flexibility into research schedules, spend time building trust, collaborate with all levels of care home staff prior to data collection, increase research capacity in care home staff and co-design research projects.